Reflections on How Designers Design With Data - Bigelow, Alex; Drucker, Steven; Fisher, Danyel; Meyer, Miriah (AVI 2014 International Working Conference on Advanced Visual Interfaces, 2014)
In recent years many popular data visualizations have emerged that are created largely by designers whose main area of expertise is not computer science. Designers generate these visualizations using a handful of design tools and environments. To better inform the development of tools intended for designers working with data, we set out to understand designers' challenges and perspectives. We interviewed professional designers, conducted observations of designers working with data in the lab, and observed designers working with data in team settings in the wild. A set of patterns emerged from these observations from which we extract a number of themes that provide a new perspective on design considerations for visualization tool creators, as well as on known engineering problems.
Winner, Best Paper Award